Materials and Technology : historical overview - Jamar, Nina (Materiali in tehnologije, 2008)
This article describes the evolution of the scientific journal Materials and Technology (Materiali in tehnologije) from its predecessors, the Iron and Steel Journal (Železarski zbornik) and Metals Alloys Technologies (Kovine zlitine tehnologije). We present the statistical data for the journal relating to the years 2000-2006. The article looks at the electronic form of the journal and the influence of online publishing on the recognition and citing of Materials and Technology around the world. We show how the process of publishing the scientific journal takes into account ISO 9000. The article concludes with a description of how Materials and Technology will develop in the future.
Keywords: serijske publikacije; Materiali in tehnologije; zgodovinski pregledi